2009
DOI: 10.1101/gad.1876110
|View full text |Cite
|
Sign up to set email alerts
|

The histone variant macroH2A1 marks repressed autosomal chromatin, but protects a subset of its target genes from silencing

Abstract: MacroH2A1 is a histone variant that is enriched on the inactive X chromosome (Xi) in mammals and is postulated to play an important, but unknown, role in the repression of gene expression. Here we show that, although macroH2A1 marks repressed autosomal chromatin, it positively regulates transcription when located in the transcribed regions of a subset of its target genes. We used chromatin immunoprecipitation (ChIP) coupled with tiling microarrays (ChIP–chip) to determine the genomic localization of macroH2A1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
239
4
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(269 citation statements)
references
References 45 publications
23
239
4
3
Order By: Relevance
“…Both studies, however, also pointed out that a small number of genes are expressed while harboring macroH2A nucleosomes on the promoter and/or the transcription start site proximal transcribed region. Moreover, Gamble et al further demonstrated that macroH2A is required for inducible activation of a set of target genes [41], thereby corroborating and extending on the earlier observation that macroH2A1.1 was required for the heat shock-mediated activation of Hsp70.1 [42]. In addition, many of the differentiation genes that were not fully activated in macroH2A1-deficient ES cells were also enriched for macroH2A in undifferentiated cells.…”
Section: Is Macroh2a Also a Gene 'Activator'?supporting
confidence: 60%
See 1 more Smart Citation
“…Both studies, however, also pointed out that a small number of genes are expressed while harboring macroH2A nucleosomes on the promoter and/or the transcription start site proximal transcribed region. Moreover, Gamble et al further demonstrated that macroH2A is required for inducible activation of a set of target genes [41], thereby corroborating and extending on the earlier observation that macroH2A1.1 was required for the heat shock-mediated activation of Hsp70.1 [42]. In addition, many of the differentiation genes that were not fully activated in macroH2A1-deficient ES cells were also enriched for macroH2A in undifferentiated cells.…”
Section: Is Macroh2a Also a Gene 'Activator'?supporting
confidence: 60%
“…In mouse liver chromatin, for instance, macroH2A1 was found to be depleted from the transcribed regions of most active genes [39,40]. Two other genome-wide studies later confirmed in other cell types that macroH2A occupancy had a general negative correlation with transcriptional future science group activity [28,41]. Both studies, however, also pointed out that a small number of genes are expressed while harboring macroH2A nucleosomes on the promoter and/or the transcription start site proximal transcribed region.…”
Section: Is Macroh2a Also a Gene 'Activator'?mentioning
confidence: 94%
“…In vivo, macroH2A is enriched on the transcriptionally inactivated female X chromosome, senescence-associated heterochromatic foci (SAHF), and large transcriptionally silent domains (Costanzi and Pehrson 1998;Zhang et al 2005;Gamble et al 2010;Tolstorukov et al 2012). macroH2A localization to the inactive X is disrupted when Xist RNA is deleted, suggesting a role for this essential cisregulatory RNA in macroH2A recruitment (Csankovszki et al 1999).…”
Section: H2az Deposition and A Futile Cyclementioning
confidence: 99%
“…3). macroH2A macroH2A localization on the inactivated female X chromosome, silent SAHF, and large transcriptionally silent domains (Costanzi and Pehrson 1998;Zhang et al 2005;Gamble et al 2010;Tolstorukov et al 2012) suggests a role in transcriptional repression, although macroH2A is not required for X-chromosome inactivation (Changolkar et al 2007). Genome-wide studies in human NT2 cells have shown that macroH2A is enriched at developmentally regulated genes, including overlap with the PRC2 complex.…”
Section: H2abmentioning
confidence: 99%
“…While macroH2A is highly enriched on the inactive X chromosome, 57 H2A-Bbd is depleted from this chromosome. In addition, macroH2A associates with several inactive promoters, 58,59 whether H2A-Bbd is expected to be found on active genes. 60 Because H2A.Z is found on active promoters, it will be very interesting to characterize the dynamics and interrelations between these three H2A variants.…”
Section: What Recruits and Removes The Randomly-incorporatedmentioning
confidence: 99%